Investigating the mediating role of self-construal on the relationship between cultural group (Malay and Australian) and the characteristics and functional use of autobiographical memory. Issue 8 (14th September 2019) - Jobson, Laura; Whittles, Nina; Tsecoutanis, Eleana; Raj, Sanjana; Yew, Rui Ying; Haque, Shamsul
ABSTRACT: Cultural differences in autobiographical memory characteristics and function have often been presumed to be associated with different cultural beliefs related to the self. The current research aimed to investigate whether self-construal mediated the relationship between cultural group and the characteristics and functional use of autobiographical memory. Caucasian Australians ( n = 71) and Malay Malaysians ( n = 50) completed an online questionnaire that included the Self-Defining Memory task, the Thinking About Life Experiences Revised Questionnaire and the Self Construal Scale. As expected, the Australian group provided longer, more autonomously oriented, specific memories than the Malay group. However, contrary to our predictions, self-construal did not mediate the relationships between cultural group and memory characteristics. The Malay group reported more frequently using autobiographical memories for self-continuity than the Australian group. Finally, there was support for an indirect pathway between cultural group and use of autobiographical memories for self-continuity and social-bonding through self-construal (i.e. independent self relative to interdependent self). The findings highlight the importance of explicitly examining values assumed to be associated with autobiographical remembering, and relating these values to memory characteristics and function.